Deutschlandbilder in der polnischen Literatur: Wie literarische Narrative gesellschaftliche Konflikte verstärken - Wolting, Monika (70 Jahre Germanistik in Zadar: Rückblicke, Einblicke, Ausblicke, 2026)
This study examines the function of literature as a medium for perpetuating conflict in post-conflict societies in Eastern Europe, focusing on the portrayal of Germany in Polish literature since 2010. Based on the premise that literature acts as a “subversive medium” that eludes direct control and activates individual processes of reflection, the analysis demonstrates how historical traumas are perpetuated in narrative structures and, indeed, how societal resentments are stabilized. The predominantly negative portrayal of Germany functions not only as a reproduction of traditional enemy images but also as a means of identity reaffirmation through demarcation. Central to this is the “solitude of reading” in which readers can internalize prejudices and affective patterns unfiltered, hindering emotional Europeanization and social integration. Since few works develop alternative, relieving images of Germany, conflict-laden narratives dominate, fostering intergenerational traumatization. Methodologically, the study combines discourse-analytical approaches with comparative text analysis to reveal typical patterns of conflict resolution and their social effects.